Assessment of ITU-R conversion method for 1-minute integration time of precipitation intensity in Malaysia - Khairolanuar, Muhamad Haziq; Ismail, Ahmad Fadzil (IEEE Computer Society, 2014)
A study has been embarked with the aim to identify the best formulation capable of obtaining statistics of precipitation intensity at 1 - minute integration time from longer integration times. Few years back, t he ITU - R has proposed a conversio n method claimed to be capable of generating precipitation intensity at 1 - minute integration time . Measurement data of precipitation intensities collect ed in Kuala Lumpur, Malaysia between 1996 and 1998 has enabled the compilation of statistics at several integration times of interest. The generated 1 - minute statistics using ITU - R method were then compared with those of measured in order to assess the method’s dependability. This paper highlights the findings drawn from the evaluation process. It can be sug gested that the ITU - R’s conversion method appears to be capable of producing consistent statistics for 1 - minute integration time from various other integration times. In addition, the paper also proposes new values for constants in the conversion formula t hat has been derived based on measured data